Formulating an Accounting Education Objectives Concept: Based on The Sluku-Sluku Bathok Song - Binti Shofiatul Jannah; Alvien Gunawan; Titik Agus Setiyaningsih; Ni Made Intan Priliandani (Universitas Hayam Wuruk Perbanas, 2025)
This study is motivated by indicating that accounting is vulnerable to using only rational reason. The dominance of rational reason in accounting education is inseparable from the agency theory taught by accounting educators. Therefore, this study aims to build a concept of accounting education objectives based on the “sluku-sluku bathok” song. This study uses Fairclough's (1992) discourse analysis, which includes text analysis, discursive practices, and social practices. The text analysis stage identifies the lyrics of the